The foundation of political science: Historical questions about its emergence and consolidation - Setti, Gabriel Augusto Miranda (Seven Editora, 2024)
What will be tried to be explained in this article is the path taken by political science, from its emergence to contemporaneity. What is sought to be apprehended is then the path of formation of a Discipline, or of a branch of study that is practiced all over the world. One cannot leave aside its origins, which come from philosophy, through sociology, more specifically political sociology, until we reach the contemporary world and the consolidation of this area of study as a discipline taught in the most diverse universities around the globe. DOI:https://doi.org/10.56238/sevened2024.026-007